Making an Impact in Community Athletics: Teaching Sport Psychology to High School Coaches - Kristin Mauldin; Ed Garrett (Journal of Scholarly Engagement)
The Coaches’ Clinic was created in order to 1) serve the community by teaching concepts and techniques in sport psychology to Riverside Unified School District (RUSD) high school coaches, and 2) to provide a training opportunity for students in the Master of Science Sport and Performance Psychology (MS SPP) program at California Baptist University. The Coaches’ Clinic was formed as a result of a collaboration with RUSD and served to support RUSD’s Three C’s Initiative (Community, Character, Conditioning).Three 3-hour workshops were conducted over three different seasons to cover all of the coaches’ offseasons. These workshops were evaluated by the attending coaches. The results of these evaluations are presented followed by a discussion of the benefits of these workshops as well as areas of improvement. Finally, reflection is given to the benefit to the MS SPP graduate students and faculty.